2020
DOI: 10.1186/s12916-020-01780-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the common MTHFR 677C→T polymorphism on blood pressure in adulthood and role of riboflavin in modifying the genetic risk of hypertension: evidence from the JINGO project

Abstract: Background Genome-wide and clinical studies have linked the 677C→T polymorphism in the gene encoding methylenetetrahydrofolate reductase (MTHFR) with hypertension, whilst limited evidence shows that intervention with riboflavin (i.e. the MTHFR co-factor) can lower blood pressure (BP) in hypertensive patients with the variant MTHFR 677TT genotype. We investigated the impact of this common polymorphism on BP throughout adulthood and hypothesised that riboflavin status would modulate the genetic risk of hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Even when folate availability is sufficient, deficiency of, another co-factor of MTHFR, can further reduce the residual MTHFR activity and thus limit the production of 5-MTHF. In this context, B2 deficiency has been found to increase the genetic risk of hypertension in individuals with the TT genotype [ 14 , 48 ]. However, remethylation of HCY is only of importance when methionine uptake via the food is low.…”
Section: Hcy B-vitamins and Cvd Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when folate availability is sufficient, deficiency of, another co-factor of MTHFR, can further reduce the residual MTHFR activity and thus limit the production of 5-MTHF. In this context, B2 deficiency has been found to increase the genetic risk of hypertension in individuals with the TT genotype [ 14 , 48 ]. However, remethylation of HCY is only of importance when methionine uptake via the food is low.…”
Section: Hcy B-vitamins and Cvd Riskmentioning
confidence: 99%
“…The common MTHFR C677T polymorphism is associated with a reduced enzyme activity, which can limit the availability of 5-MTHF in situations when folate supply is low [ 13 ]. Recent evidence suggests that riboflavin in the form flavin adenine dinucleotide (FAD) is a cofactor for MTHFR and may thus represent a key factor linking the MTHFR C677T polymorphism to CVD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the association between the SNPs of the folate metabolizing genes Methylenetetrahydrofolate reductase (MTHFR) and Methionine synthase (MTR) genes with the changes that alter the primary structure of each protein, decrease enzymatic activity. This causes modification in DNA methylation profiles, abnormal gene expression and inactivation of tumor suppressor genes (4,13).…”
Section: Discussionmentioning
confidence: 99%
“…33 However, an observational data revealed that MTHFRTT genotype in 18-70 year old adults was associated with an increased risk of hypertension (systolic BP ≥ 140 and/or a diastolic BP ≥ 90 mmHg). 34 In addition, it was noted that the MTHFR C677T polymorphism significantly increased the risk of hypertension in rural Indonesian-Sudanese population. 35 On the other hand, although 65% of the studied subjects have diabetic complications, we could not find any association between the MTHFR C677T genotype distribution and the prevalence of CVD, DN and DR among the studied population (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, an observational data revealed that MTHFRTT genotype in 18–70 year old adults was associated with an increased risk of hypertension (systolic BP ≥ 140 and/or a diastolic BP ≥ 90 mmHg). 34 In addition, it was noted that the MTHFR C677T polymorphism significantly increased the risk of hypertension in rural Indonesian‐Sudanese population. 35 …”
Section: Discussionmentioning
confidence: 99%